He neuroendocrine peculiarities of essential arterial hypertension development - Virajitha, M.; Lukashenko, L. V.; Vamsi, V.; Likhasenko, I. V.; Лукашенко, Ланна Віталіївна; Лихасенко, Іветта Валеріївна (My University, 2018)
To investigate the potential role of neuropeptide Y (NPY) and vasoactive intestinal peptide (VIP) in the pathogenesis of essential arterial hypertension (EAH).
Keywords: Essential hypertension; neuropeptide Y; vasoactive intestinal peptide; endocrine